Étude paléodémographique et utilisation du feu à Hili N, une sépulture collective en fosse de la fin de l’âge du Bronze ancien aux Émirats Arabes Unis - Esther Gatto; Gautier Basset; Sophie Méry; Kathleen McSweeney (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
In 1983, next to one of the monumental circular tombs considered to be diagnostic for the Umm an-Nar Period (ca 2700-2000 BC), a collective burial in a pit-grave was discovered. The first objective of the present study is to establish whether this structure, dated to 2200-2000 BC, i.e. the end of the Early Bronze Age in the region, is associated with a specific funerary practice or to a selection of the buried individuals. The second is to define the function of the fire in the pit. All the deceased aged more than one year were buried without any perceptible selection as to age or sex. However, some of the babies aged less than twelve months were probably buried elsewhere.At least four fires occurred during the last phases of use of the grave. The significance of these fires - ideology, ritual, utilitarian – is unknown. We can only confirm that these fires were not intended to burn all the bones, nor a particular individual.